2020
DOI: 10.21203/rs.3.rs-111425/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of low-sugar and High-dietary Fiber Noodles on Glycemic Response in Healthy Humans: A Cross-over Trial

Abstract: Background: Low-carbohydrate diets are popular nutritional therapeutics based on recommendations of the American Diabetes Association (2013). In previous reports, we suggested a new diet-intake restriction method using low-sugar, high-dietary fiber noodles containing okara and konjac and reported their effect on blood glucose levels in healthy animals and animal models of type 2 diabetes. This study aimed to compare the effect of low-sugar, high-dietary fiber noodles with that of normal wheat noodles on glycem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…We investigated the impact of LS-HDFNs consumption on the glycemic response in healthy individuals in a crossover trial using a single meal test. We found that subjects who consumed LS-HDFNs had signifcant attenuation of the increase in postprandial blood glucose and insulin levels compared to subjects who consumed normal wheat noodles [16]. Our results are in line with those of our previous reports.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We investigated the impact of LS-HDFNs consumption on the glycemic response in healthy individuals in a crossover trial using a single meal test. We found that subjects who consumed LS-HDFNs had signifcant attenuation of the increase in postprandial blood glucose and insulin levels compared to subjects who consumed normal wheat noodles [16]. Our results are in line with those of our previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrated the impact of LS-HDFNs consumption on blood glucose levels in type 2 diabetes mouse and rat models in previous studies [15]. In addition to these reports, we described the impact of LS-HDFNs on glycemic response in healthy individuals in a crossover trial using a single meal test and reported that individuals who consumed LS-HDFNs had signifcantly reduced postprandial blood glucose and insulin levels than healthy individuals who consumed normal wheat noodles [16]. Nevertheless, there is no experimental evidence on the body weight of healthy humans who consume LS-HDFNs for 28 days.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…With this background, we had previously studied the effects of food and food products on human health (Kadokura et al, 2020(Kadokura et al, , 2021a and have noted the possible beneficial effects of fish paste products used in Japanese traditional foods. In this study, we examined the effect of consumption of fish paste products used in Japanese traditional foods on aged rats and extrapolate the implications of their consumption on human health.…”
Section: Introductionmentioning
confidence: 99%